An experimental study of a thermochemical regeneration waste heat recovery process using a reformer unit. (15th July 2018) - Gaber, Christian; Demuth, Martin; Prieler, René; Schluckner, Christoph; Hochenauer, Christoph
Abstract: This paper presents a thermochemical regenerative heat recovery process for utilizing the waste heat of oxy-fuel furnaces, with three significant modifications compared to current state-of-the-art reforming concepts. (I) Experimental tests with a reformer test rig were performed, in order to investigate the bi-reforming of methane into syngas by using water and carbon dioxide with a steam-to-carbon ratio of 0.5. The measured syngas concentrations were compared to calculated equilibrium values and carbon deposits were determined. A methane conversion rate of 95.3% was achieved. (II) Carbon deposits in a regenerator bed are usually burned with purge gases. In contrast to this procedure, oxygen was added to the fuel/exhaust gas mixture in order to cause tri-reforming of methane with a steam-to-carbon ratio of 0.4. The syngas concentrations were compared to equilibrium values and it was found, that tri-reforming significantly reduces carbon formation. A methane conversion rate of 96.7% was achieved. (III) Furthermore, reforming and regeneration cycles were coupled and it was found that the temperature profile within the TCR regenerator bed material varies greatly from that of a common regenerator. Regeneration with water and carbon dioxide was sufficient to eliminate all carbon deposits. Highlights: Bi-reforming of methane using CO2 and H2O with a steam to carbon ratio of 0.5. Tri-reforming of methane using O2, CO2 and H2O with a steam to carbon ratio of 0.4. Reduction of carbon formation as a result of regenerative bi-reforming. Investigation of the temperature profile and cycle time of a TCR reformer unit.